Platinized graphene fiber electrodes uncover direct spleen-vagus communication - Maria A. Gonzalez-Gonzalez (Nature Portfolio, 2021)
Gonzalez-Gonzalez et al. use high-performance platinized graphene fiber electrodes to interface individual neurovascular plexus that innervate the spleen. Their approach provides evidence for distinct function of individual spleen terminal branches in organ function.